INNOVATIVE SYSTEM WITH SIMULTANEOUS ENERGY RECOVERY IN SHIPS FOR COMPLETE DESULPHURISATION OF EXHAUST GAS DERIVED BY HEAVY OIL - Pittas, N.; Koutsoukos, P.; Moutsios, Vasileios; Muravieva, I. (International Journal of Engineering Technologies and Management Research, 2021)
This paper presents an innovative worldwide method of total of gas combustion-derived ships on heavy fuel diesel engines. For the treatment of waste aqueous solution derived from with aqueous solution NaOH the exhaust gas and capture the S from . For the treatment wastewater plant is necessary to have big surface and quantity of salt water. But unfortunately, the space free on the ships are very restricted and further consequently born stability problems for the ships. This proposal innovative methodology with new approx and new design overcame the limitations and the low performance of the actual scrubber systems and the negative provoked enormous environmental impact of these emissions and not complies the IMO international regulations. The method exposed in this paper overcame the requirement its international regulations of IMO (international maritime organization) and is Patent N. Pittas .